Study on Shashi Deshpande’s Views on Feminism in Her Novel (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Shashi Deshpande happens to be one among these writers who has taken up this issue of woman liberation. She is without a doubt the most noteworthy of the contemporary Indian ladies’ novelists who have depicted her ladies in their hardships under the effect of custom and feminism. Various ladies’ writers started to manages the topic of impression and persecution of the ladies. Shashi Deshpande is one of the critical novelists in Indian literature. She is extensively celebrated as one of the capable beauticians and inventive writers of her age. Subsequently, we have to go for a nearby investigation of Shashi Deshpande's books as a genuine impression of feminism. Before, the work by the lady’s creators has consistently been underestimated as a result of some male centric presumptions. Feminism is a statement of hatred at the out of line treatment distributed to any woman. In literature, it alludes to any mode that moves toward a book with preeminent worry for the idea of female experience. The disparities against which the women's activist have raised their voice of dissent legitimate, financial matters and social limitation on the essential privileges of woman can be followed from the beginning of time.